Prevalence and Associated Factors for the Development of Anterior Open Bite and Posterior Crossbite in the Primary Dentition - Sousa,Raulison Vieira de (2014)
The aim of the study was to verify the prevalence of anterior open bite (AOB) and posterior cross-bite (PC) in the primary dentition and the association with sociodemographic factors, presence and duration of nutritive and non-nutritive habits. A cross-sectional study was carried out with 732 preschoolers in Campina Grande, PB, Brazil. Clinical exams were performed by three calibrated examiners (Kappa: 0.85-0.90). A questionnaire addressing sociodemographic data as well as nutritive and non-nutritive sucking habits was administered to parents/caregivers. Data analysis involved descriptive statistics and Poisson regression analysis (α=5%). The prevalence of AOB and PC was 21.0% and 11.6%, respectively. AOB was significantly associated with the three-year-old age group (PR: 1.37; 95%CI: 1.24-1.52), enrollment in public school (PR: 1.09; 95%CI: 1.01-1.17) and duration of pacifier sucking ≥36 months (PR: 1.41; 95%CI: 1.30-1.53). PC was associated with pacifier use (PR: 1.11; 95%CI: 1.05-1.17) and duration of breastfeeding <12 months (PR: 1.05; 95%CI: 1.00-1.10). Socioeconomic factors appear not to be related to AOB or PC in the primary dentition, except type of preschool. Breastfeeding should be encouraged for longer periods and the use of pacifier beyond 3 years of age represents a predisposing factor for both types of malocclusion, especially AOB.